2020
DOI: 10.1016/j.apmr.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cerebral Palsy in Adulthood: A Systematic Review and Meta-analysis of the Most Frequently Studied Outcomes

Abstract: To describe the epidemiology of health status, impairments, activities and participation in adults with cerebral palsy (CP). Data Sources: Embase, MEDLINE, Web of Science, PsycINFO, Cumulative Index to Nursing and Allied Health, Cochrane, and Google Scholar were searched for 3 themes ("cerebral palsy," "adult," and "outcome assessment") in literature published between January 2000 and December 2018. Study Selection: Full-article peer-reviewed English journal articles on descriptive, observational, or experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 102 publications
4
58
0
Order By: Relevance
“…12,58,59 Estimates of fatigue prevalence range from 64% to nearly all adults with CP. 5,12,56 Chronic fatigue correlates with lower life satisfaction and significant worry in this population. 57,60 The factors contributing to chronic fatigue in CP are unclear, and the methods by which this fatigue can be optimally addressed are similarly undefined.…”
Section: Chronic Fatigue and Sleep Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…12,58,59 Estimates of fatigue prevalence range from 64% to nearly all adults with CP. 5,12,56 Chronic fatigue correlates with lower life satisfaction and significant worry in this population. 57,60 The factors contributing to chronic fatigue in CP are unclear, and the methods by which this fatigue can be optimally addressed are similarly undefined.…”
Section: Chronic Fatigue and Sleep Disordersmentioning
confidence: 99%
“…5,68 Numerous studies find that adults with CP experience significantly more pain than those without CP. 5 However, the majority of adults with CP and pain do not seek pain treatment. 69 As a result, there is a huge unmet need for pain relief among this population.…”
Section: Chronic Fatigue and Sleep Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Studies have also reported increased fatigue, incidence of falls, pain and a decline in mobility, as people with CP move into adulthood. [15][16][17] Therefore, adults with CP may require extensive health services. The National Institute for Health and Care Excellence (NICE) guideline for CP in adults has recommended continuity of care for adults with CP, tailored to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have focussed on the epidemiology of CP in adults, quality of life, pain and effectiveness of interventions used by adults with CP. 16 30–32 There is a need for a theory informed review with broader perspectives on health service use among adults with CP, rather than focussing on the effectiveness of any specific intervention. Such a review would potentially inform health service used by adults with CP, direct research efforts and identify areas of challenges faced by adults with CP.…”
Section: Introductionmentioning
confidence: 99%